Prosedur Perpanjangan Sertifikat Ship Sanitation Control Exemption Certificate (SSCEC) di Kantor Kesehatan Pelabuhan Kelas I Dumai Oleh PT. Pelayaran Cahaya Papua Cabang Dumai - Riko Andreas Simbolon; Syarifur Ridho; Suratni Ginting (Jurnal Bisnis Kreatif dan Inovatif, 2024)
PT. Pelayaran Cahaya Papua Dumai Branch is one of the companies operating as a Shipping Agency (ship agency) which provides domestic and international services. PT. Pelayaran Cahaya Papua also provides ship services such as ship needs (reflagging, fresh water, bunker), and also provides services for processing ship certificates that are entering their expiry date. The discussion presented in this paper is the Ship Sanitation Control Exemption Certificate (SSCEC) Certificate Extension Procedure at the Class I Port Health Office (KKP) by PT. Dumai branch of the Papua Light Cruise. In the Ship Sanitation Control Exemption Certificate (SSCEC) Certificate Extension Procedure, the company deals directly with relevant agencies, both government and private (companies). By having a good relationship with the shipowner (ship owner) who has been given the authority to make a Letter of Appointment (LOA) agreement to agent their ships, the Company can more freely convey information regarding ship certificates because information regarding ship certificates has a very important role in managing the arrival and departure of ships. To obtain data, the author used 2 (two) types of observation methods in collecting data, namely direct observation of field study and library study. Thus the author can conclude that the procedure for extending the Ship Sanitation Control Exemption Certificate (SSCEC) at the Class I Port Health Office (KKP) has been running smoothly.